Integrating Entrepreneurship Education in Islamic Boarding Schools: Strategies for Empowering Students' Entrepreneurial Spirit - Junaidah, Junaidah; Meisuri, Meisuri; Sari, Mayang; Nurbaiti, Syarifah; Mahardika, Nikita Putri (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
The purpose of this study was to synthesise the concept of entrepreneurial leadership, identify the independence program of Islamic boarding schools, and analyse leadership strategies in developing the entrepreneurial spirit of students. This study employs a qualitative approach, utilising a case study design, where data are collected through interviews, observations, and documentation. The data are then analysed in three stages: data reduction, data presentation, and conclusion. The results of the study indicate that Islamic boarding schools integrate entrepreneurship education into their curriculum to equip students with practical skills that can be applied after graduation. Entrepreneurship programs, such as Job Training Centres and Cooperatives, as well as other economic sectors, aim to increase the financial independence of students, create jobs, and reduce unemployment. This approach to integrating religious education and entrepreneurship allows students to make positive contributions to society after graduation. This study suggests that fostering an entrepreneurial spirit in Islamic boarding schools can be an effective alternative educational model for enhancing students' economic independence. The integration of religious education and entrepreneurship prepares students to become entrepreneurial leaders who are economically prosperous and have spiritual values.